(NaSTROFIZIKA KOSMI^ESKIH LU^EJ (B/s - (NbEREZINSKIJ(B, (NwENIAMIN sERGEEWI^s; (NbULANOW(B, (Ns(B. (Nw(B.s; (NgINZBURG(B, (NwITALIJ lAZAREWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 493-524 (202 (NNAZW(B.)s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NaSTROFIZIKAs; (NkOSMI^ESKIE LU^Is